Building an integrated capital market in East Asia - Robert N. McCauley (Asian Development Bank Institute (ADBI), 2007)
This paper takes stock of the state of financial integration in East Asia. It contrasts the international integration of equity markets, the regional integration of the markets for bonds and syndicated loans denominated in US dollars, and the insularity of most local currency bond markets. In the last, it finds that the regional issuance in the Japanese foreign bond ('Samurai') and euroyen markets did not recover from the shocks during and after the Asian financial crisis. However, it finds a strong element of regional integration in the 'Uridashi' market in which Japanese investors have bought relatively large sums of Australian and New Zealand dollar bonds. Regional central banks have sought to jump-start development of domestic bond markets by investing limited amounts of their official foreign exchange reserves in each other's domestic bond markets. The willingness of Japanese investors to take on the currency risk of the Australian and New Zealand dollars offers hope that capital can flow within the region without the vehicle of an extra-regional currency. The largely global integration of East Asian equity markets highlights the risk of opening bond markets to global investors if institutional investors in the region remain sidelined in domestic assets. Without a substantial regional bid for equities, investors in individual economies can end up bearing the brunt of heavy selling by global investors. If institutional investors in the region were able to invest more abroad, they could help lend stability to local bond markets.
Keywords: G1; H63; O16; 330; Finanzmarkt; Marktintegration; Ostasien